Answer:
See below
Step-by-step explanation:
The equivalence you are required to use is the following:
t→s ⇔ ¬t∨s
This also implies, negating both statements and using De Morgan's Laws
¬(t→s) ⇔ t∧¬s (*)
a) Here t=¬p and s=¬q. Hence ¬p → ¬q ⇔ ¬¬p∨¬q ⇔ p∨¬q
b) Here t=p∨q and s=¬p. Thus (p ∨ q) → ¬p ⇔ ¬(p ∨ q) ∨ ¬p ⇔ (¬p∧¬q)∨¬p (this last step is by De Morgan's Laws)
c) Here t= (p → ¬q) and s=(¬p → q), therefore
(p → ¬q) → (¬p → q) ⇔ ¬(p → ¬q)∨(¬p → q) ⇔ (p∧¬q)∨(¬¬p∨q) ⇔ (p∧¬q)∨(p∨q)
We have to apply he equivalences twice. In the last part we used (*) to negate the conditional, and applied the equivalence to ¬p → q.